Manajemen Berbasis Komunitas untuk Pengembangan Kota Lama Semarang Berwawasan World Heritage - Dewi Yuliati; Endang Susilowati; Titiek Suliyati (Endogami: Jurnal Ilmiah Kajian Antropologi, 2019)
This article contains the discussion on Semarang community based management to endorse the development of the Site of Semarang Old City which has been already proposed to UNESCO to obtain the world heritage status. One of the UNESCO requirements for obtaining the world heritage status is community involvement in conservation and developing the cultural heritage, so this study is focusing on the involvement of the Old City communities in the developing of Semarang Old City cultural heritages toward the world heritage status. The communities involved are namely: AMBO (Asosiasi Masyarakat Bangun Oudestad), Oen Semarang Foundation, Monod Diephuis, dan KPS (Komunitas Pegiat Sejarah). The result of this research shows that these communities have the great involvements in developing Semarang Old City to welcome its status as a world heritage.